Effects of electrical stimulation in early Bells palsy on facial disability index scores - P. Alakram; T. Puckree (AOSIS, 2011)
Recovery following facial nerve palsy is variable. Physiotherapists try  to restore  function  in  patients  with  Bell's  palsy.  The  choice  of treatment modality  depends  on  the  stage  of  the  condition.  Although limited  evidence  exists  for  the  use  of  electrical  stimulation  in  the acute  stage  of  Bell's  palsy, some physiotherapists in South Africa have been applying this modality. This study examined the effects of electrical stimulation on functional recovery from  Bell's palsy using the Facial Disability Index, a tool that documents recovery from the patients' perspective. A two group pre-test post-test experimental design comprising of 16 patients with Bell's Palsy of less than 30 days duration was utilized. Patients with a clinical diagnosis of Bell's Palsy were systematically allocated to the control and experimental groups. Patients (n=16) were pre-tested and post-tested using the Facial Disability Index. Both groups were treated with heat, massage, exercises and given a home program. The experimental group also received electrical stimulation. The FDI of the control group improved between 17, 8% and 95, 4% with a mean of 52, 8%. The improvement in the experimental group ranged between 14, 8% and 126% with a mean of 49, 8%. Certain clinical residuals persisted in a mild form in both groups on discharge from the study.  The effects of electrical stimulation as used in this study during the acute phase of Bell's palsy, quantified as the FDI was clinically but not statistically significant. A larger sample size, longer stimulation time or both should be investigated.